A review of theories and models applied in studies of social media addiction and implications for future research. (March 2021) - Sun, Yalin; Zhang, Yan
Highlights: 25 theories/models guiding 55 social media addiction (SMA) studies are reviewed. Perspectives and constructs explaining the development of SMA are discussed. Limitations of those theories/models and future research areas are presented. Abstract: With the increasing use of social media, the addictive use of this new technology also grows. Previous studies found that addictive social media use is associated with negative consequences such as reduced productivity, unhealthy social relationships, and reduced life-satisfaction. However, a holistic theoretical understanding of how social media addiction develops is still lacking, which impedes practical research that aims at designing educational and other intervention programs to prevent social media addiction. In this study, we reviewed 25 distinct theories/models that guided the research design of 55 empirical studies of social media addiction to identify theoretical perspectives and constructs that have been examined to explain the development of social media addiction. Limitations of the existing theoretical frameworks were identified, and future research areas are proposed.